Path Loss of Indoor Hotspot and Indoor Factory Environments for 5G Wireless Networks - Al-Mejibli, Intisar; Mohammed, Hussein A.; Hoomod, Haider Kadhim; Nawaf Rasheed Alharbe (Journal of Engineering and Sustainable Development, 2025)
The increased exploration of wireless communication networks in various fields has significant implications for automating daily human tasks and creating smart environments. However, to make such implementations successful, it is essential to investigate the characteristics of wireless channels. Path loss is a fundamental factor in wireless network communications and measures signal strength. The main objective of this proposal is to identify the criteria to be considered when designing and developing wireless sensor network WSN applications for indoor hotspot (InH) and indoor factory (InF) environments. This research investigates the 3GPP Indoor model in (InH) and (InF) environments. It considers the impact of Line-of-Sight (LOS), Non-Line-of-Sight (NLOS), and human blockage on path loss. Further, the InH scenario has been compared to the InF scenario. The results show that path loss in NLOS conditions is more variable than in LOS conditions, regardless of the human obstruction. In general, the results demonstrate the difference in path loss between InH and InF scenarios falls within a range of 9.1275–7.175 dB.